PWE-094 Monitoring heart rate variability during acute decompensation predicts mortality and risk of recurrent hospitalisation. (22nd June 2015) - Sawhney, R; Chatterjee, D; Gallego Leon, A; Jalan, R; Mookerjee, R
Abstract : Introduction: In advanced cirrhosis, hospital admissions are common and mortality high from intercurrent illness, often associated with increased inflammation. The aim of this study was to use heart rate variability (HRV), previously correlated with cirrhosis severity, to determine patient outcome following admission to hospital with acute decompensation. Method: Using a wireless-monitoring technology, Lifetouch®, we assessed HRV remotely (parameters- SDNN and RMSSD) in 32 patients (69% male; mean age 51.8 ± 12.3 years; 75% alcoholic cirrhosis) admitted to Royal Free Hospital with acute decompensation. Patients were followed until discharge and data collected on subsequent death, transplantation or last follow-up date to assess re-admission rate and disease severity. HRV data was compared with clinical and biochemical indices and correlated to patients' outcome. Results: HRV, as determined by SDNN, was significantly lower in patients who died or who required liver transplantation (p = 0.005). Lower SDNN was associated with the presence of ACLF (p = 0.006). SDNN inversely correlated with Child-Pugh, MELD-Na and CLIF-AD scores (p ≤ 0.0001 for all; r=-0.47, -0.52 and -0.62 respectively). ROC curve analysis demonstrated utility of SDNN for predicting mortality (AUC 0.81; p = 0.006) and this was better than Child-Pugh, MELD-Na and CLIF-AD in this cohort. Based on this analysis, an SDNN cut-off of 19.65 ms for predicting death was selected with sensitivity 100%, specificity 57% and NPV 100% (p = 0.004). Further application of this cut-off using time-to-event analyses showed patients with SDNN >19.65 ms had significantly longer transplant-free survival (p = 0.004). Amongst patients discharged from hospital, there was a trend to delayed readmission with an SDNN >19.65 ms (p = 0.07). Three patients died or were transplanted during their index admission and all had very low SDNN (<11 ms). 67% of patients with subsequent readmission (median 109 days from discharge) and 75% with multiple admissions had SDNN <19.65 ms. HRV measured by both SDNN and RMSSD correlated with white-cell count (SDNN r=-0.31, p = 0.002; RMSSD r=-0.47, p = 0.017). Conclusion: This study shows HRV to be an important prognostic criterion for mortality, transplant–free survival and risk for readmission following acute decompensation of cirrhosis. Furthermore, HRV correlates with increased inflammation following acute decompensation. Our data suggests HRV monitoring may have utility in identifying need for early intervention in patients discharged home after an episode of acutely decompensated cirrhosis. Disclosure of interest: None Declared.